Moderation of Religion Between Muhammadiyah, Nahdlatul Ulama (NU) and Christian in Tegal Rejo Village, Medan Perjuangan Subdistrict - Ervina Putri Wulandari; Fadia Annisa; Meidya Ningsih; Fharcha Fahrica; Zahratul Idami (Pena Cendekia Insani, 2021)
An attitude or behavior that always prioritizes the middle way values and does not overdo it can be understood as religious moderation. Muslim organizations Muhammadiyah and the Nahdlatul Ulama (NU) in Indonesia are responsible for religious moderation. There are other religions that coexist with Islam, including Christianity. For this study, we aimed to observe the implementation of religious moderation between Muhammadiyah and Nahdatul Ulama and Christians in Tegal Rejo Village, Medan District. The descriptive analysis method is used in this study. When it comes to religious activities, the results of this study show that Tegal Rejo Village has implemented religious moderation between Muhammadiyah and NU that is mutually tolerant, respectful, and relentless. According to reports, there are no conflicts and no interference between worship services in Tegal Rejo Village, where Christians live next door. In order to live in a safe and peaceful environment, religious moderation is.